1998
DOI: 10.1292/jvms.60.1233
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella in Broiler Chickeens in Thailand with Special Reference to Contamination of Retail Meat with Salmonella Enteritidis.

Abstract: The present study was performed to assess the prevalence of Salmonella in chickens in Thailand. In 1997, 22 serovars of Salmonella were isolated from 72 of 100 chicken meat samples purchased from 10 retail markets in Bangkok and 20 of 200 chicken meat samples from one slaughterhouse for export and 19 of 285 chicken feces obtained from three farms located in the east region of Thailand. The most predominant serovar was S. Enteritidis, which was isolated from 28% of the retail chicken meat, 4.5% of the chicken m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
(17 reference statements)
3
6
1
2
Order By: Relevance
“…This signifies the fact that all these meats are more or less handled in the same manner. The findings are also closely related to the findings of several other researchers (Mead et al1994 andBoonmar et al 1998). …”
Section: Resultssupporting
confidence: 91%
“…This signifies the fact that all these meats are more or less handled in the same manner. The findings are also closely related to the findings of several other researchers (Mead et al1994 andBoonmar et al 1998). …”
Section: Resultssupporting
confidence: 91%
“…Serotyping in that study revealed the presence of S. typhimurium, S. kentucky and S. enteritidis , species that were also present in the current study. Also, some authors such as Jafari et al [21], and Boonmara et al [22], previously reported similar incidence levels of Salmonella, which were (5.8%) and (6.65%) respectively. In a previous study performed by Mohamed et al [23], in Kafr Elsheik Governorate- Egypt, Salmonella was isolated from broiler chickens with an incidence of (2.5%) and this percentage was lower than the current study.…”
Section: Discussionmentioning
confidence: 83%
“…The study showed that the retail pork was highly contaminated by Salmonella, followed by chicken meat and fresh vegetables. These products, according to many reports, are the resources of Salmonella contamination (1,2,12,13).…”
Section: Discussionmentioning
confidence: 99%